2018
DOI: 10.24176/re.v9i1.2806
|View full text |Cite
|
Sign up to set email alerts
|

IMPLEMENTASI SETS (Sceince, Environment, Technology, Social) TERHADAP LITERASI SAINS SISWA SDN 02 MOJOREJO MADIUN

Abstract: This sresearch aims to apply the SETS approach (Sceince, Environment, Technology, and Social) to improve scientific literacy through understanding science concepts, basic science process skills and scientific work on science learning for fifth grade students of SDN 02 Mojorejo Madiun City. The method used in this study is Classroom Action Research (CAR) which consists of 2 cycles. each cycle has 4 stages, namely planning, implementing, observing, and reflecting. the subjects in this study are fifth grade stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…According to Yager et al, (2012) learning using SETS focuses on processes rather than products, so that by the theory of constructivism learning oriented to the formation of knowledge through the process of finding, marking and organizing new data. In line with this opinion, Amirshokoohi (in Retno & Marlina, 2018) revealed that the SETS framework is based on an interdisciplinary constructivist philosophy that involves students actively in the learning process. Thus the learning theory that underlies the SETS learning model is the constructivism learning theory.…”
Section: Sets Learning Modelmentioning
confidence: 88%
See 2 more Smart Citations
“…According to Yager et al, (2012) learning using SETS focuses on processes rather than products, so that by the theory of constructivism learning oriented to the formation of knowledge through the process of finding, marking and organizing new data. In line with this opinion, Amirshokoohi (in Retno & Marlina, 2018) revealed that the SETS framework is based on an interdisciplinary constructivist philosophy that involves students actively in the learning process. Thus the learning theory that underlies the SETS learning model is the constructivism learning theory.…”
Section: Sets Learning Modelmentioning
confidence: 88%
“…1. The problems presented sometimes make student motivation decrease and unable to do further work as expected (Retno & Marlina, 2018). 2.…”
Section: Sets Learning Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…SETS learning will lead students to design and create new products and systems (Cetin, 2020;Smith, 2020). SETS learning is very useful in developing critical thinking skills (Kartikasari, 2018), students' scientific literacy skills (Senturk, 2018;Retno, 2018;Walton, 2019). Students who take SETS learning will have motivation and interest in learning (Walton, 2019;Rahman, 2021) and can create meaningful learning experiences (Lowery, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of science learning with the SETS approach include 1) students are faced with a problem situation to understand the benefits of learning science to a form of technology that is needed by society; 2) students analyze the possible impact that occurs in the transfer of science to technology; 3) students are asked to explain the relationship between the science concepts studied with other elements in the relevant SETS; 4) students analyze the benefits or disadvantages of using the concept of science when it is changed in the use of technology; and 5) provide opportunities for students to express ideas about solving problems in their environment by constructivism theory. Besides, (Retno & Marlina, 2018) stated that the SETS approach invites students to look for the impact of losses that may arise from the application of technology on the environment and society.…”
Section: Introductionmentioning
confidence: 99%